Forefoot deformity surgical reconstruction outcomes in people living with rheumatoid arthritis in South Africa - Mukabeta, Takura Darlington Maumbe (Division of General Surgery, 2022)
Introduction: Involvement of the forefoot is common among patients with Rheumatoid Arthritis. It results in severe deformities with significant disabilities. Aim: The aim of this study was to compare and assess in patients with Rheumatoid Arthritis in a South African population the outcomes of severe forefoot deformity reconstruction surgery in the short- to medium-term and in particular focusing on radiological, clinical, and functional outcomes. Patients and Methods: A retrospective review of 19 patients who received reconstructive forefoot surgery for forefoot deformities resulting from Rheumatoid Arthritis was undertaken. They all underwent Modified Hoffman Surgical Reconstruction (first MTPJ fusion and lesser toe resection arthroplasty). The patient records between 2013 and 2016 were reviewed. Pre-operative and post-operative outcome scores were collected. Final postoperative radiographs were analyzed. Patients completed Short Form 36 and AOFAS forefoot scores. Post-operative scores were collected 6 months post-op. Results: There were 19 patients in the study with a minimum 6 months follow up. Of the 19 patients 17 (89.5%) were females and 2 (10.5%) males. The mean age was 54.9 ± 9.6 years (range: 34 – 69 years). Most patient outcomes (SF36, AOS alignment, VAS Pain percentage, and VAS Disability percentage) significantly improved with a p value < 0.05, when comparing the pre-operative versus post-operative variable scores. However, only AOS Alignments showed no significant difference between pre-operative and post-operative scores (p>0.05). Conclusion: Reconstructive forefoot surgery with the Modified Hoffman Surgical Reconstruction provides marked radiological correction, with significant improvements in the quality of life of the cohort of patients.